The Life of Slovenian Exonyms and Their Familiarity in the Professional Community - Kladnik, Drago; Bole, David (Acta geographica Slovenica, 2012)
This article examines the lifecycle of Slovenian exonyms in which the characteristic stages are the creation of an exonym, its increasingly frequent use, its frequent and general use, its increasingly rarer use or dying out, death, and being forgotten. The findings of a similar Czech study on exonyms are briefly presented. The presentation of familiarity with Slovenian exonyms is based on an online survey that was carried out in September and October 2010. We received over 160 correctly completed questionnaires. Analyzing them increased our knowledge of familiarity with exonyms for European cities, European islands and archipelagos, and archaic exonyms for European cities that people no longer use today. We also analyzed the degree of familiarity by respondent’s ages and professions.